The Role of Parents as Role Models in Children's Moral Education - Harahap, Emilia Fitri; Khairunnisa, Khairunnisa; Araminta, Nabila; Sitorus, Masganti (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyse the role of parents as role models in moral education for children, especially in forming character and moral behaviour from an early age. Using a qualitative descriptive approach, this study relies on primary data obtained through interviews with parents and secondary data from literature studies and related documents. Data collection techniques were carried out through direct observation and in-depth interviews with subjects who were parents of children in early childhood. Data analysis was carried out descriptively by examining the patterns of parental roles and providing examples of noble morals. The study results showed that parental behaviour greatly influences children's moral development; children tend to imitate the actions and attitudes of their parents, both positive and negative. The success of this process is primarily determined by religious knowledge, the quality of interaction within the family, and collaboration with a positive educational and social environment. This confirms that parental exemplarity is the primary foundation in children's moral education.